Availability, prices, and affordability of essential medicines in Asia: A systematic review - Muhammad Qowiyul Amin, Susi Ari Kristina, Satibi Satibi (Journal of Applied Pharmaceutical Science, 2024)
Essential medicines are vital for healthcare, but nearly one-third of the global population faces challenges accessing them. World Health Organization (WHO) and Health Action International (HAI) collaborated on a manual with standardized methods for measuring drug availability, prices, and affordability to assist governments in formulating effective policies. A systematic review was conducted to analyze the availability, pricing, and affordability of essential medicines across several Asian countries. A comprehensive search was conducted across databases (Scopus, PubMed, and Google Scholar). The review targeted studies that employed WHO-HAI methods. Articles predating 2018 and those not published in English were excluded, resulting in seven articles and subsequently presented descriptively. The availability in the public sector is generally lower than in the private sector. Moreover, the overall availability in public and private sectors falls below the targets set by the WHO global action plan. Private-sector medicine prices were consistently higher than in the public sector. Affordability analysis showed that branded drugs were less accessible compared to generic drugs, with a majority of medications requiring more than one day’s income (1.1–5.2) for individuals to afford. The comprehensive assessment highlights the need for ongoing efforts by authorities to regulate and improve the availability, pricing, and affordability of essential medicines to ensure universal accessibility.
Keywords: Drug availability, prices, affordability, WHO-HAI, Asia